Forward- and Backward Looking Models for Norwegian Export Prices - Ingvild Svendsen (Statistics Norway, Research Department, 1995)
The Norwegian export price for an aggregated commodity is modelled assuming price-setting behaviour. The focus is on the choice between backward- and forward looking models. The dynamics is modelled according to three different approaches; a backward looking error correction model and two forward looking models where rational expectations are assumed. The first forward looking model is derived from a multiperiod quadratic loss function imposing backward-forward restrictions on the parameters. The results from this specification are not encouraging. We then allow data to choose the lead structure, resulting in a less restrictive forward looking model. The backward- and forward looking models are compared to an estimated cointegrating vector for the long-run solution. An encompassing test on the backward- and forward looking model indicates that further research should look for a model that encompasses both of them.
Keywords: C22; D84; F12; 330; Export prices; Imperfect competition; Multiperiod loss function; Rational expectations; Error correction models